2011
DOI: 10.1111/j.1432-2277.2011.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey to determine the views of renal transplant patients on generic substitution in the UK

Abstract: Summary Rising healthcare costs promote the generic substitution among patients because it is identifiable costs. A key concern is that patients should be involved in the decision of switching. The aim of this study was to examine renal transplant patients’ views on generic substitution in the UK. A total of 163 renal patients were surveyed using 36 multiple‐choice questions at Barts and The London Renal Transplant Clinic, in the UK. Transplant recipients over 18 years, able to read and write English and willi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 35 publications
3
54
1
1
Order By: Relevance
“…Many others would agree to accept generic substitution if they were informed clearly. This is supported by the results of a similar study on renal patients in the UK [22]. This indicates a need for educating patients and for clarifying the reasons for generic substitution and the roles of healthcare professionals in successfully introducing this practice.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Many others would agree to accept generic substitution if they were informed clearly. This is supported by the results of a similar study on renal patients in the UK [22]. This indicates a need for educating patients and for clarifying the reasons for generic substitution and the roles of healthcare professionals in successfully introducing this practice.…”
Section: Discussionsupporting
confidence: 73%
“…10/64. The questionnaire had been piloted and validated previously in the Royal London Hospital in the United Kingdom for a survey carried out in that hospital [22]. The questionnaire was available in both English and Arabic to cover all patients.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is evidence that not only doctors but also pharmacists hold negative views of generics and resist prescribing generic medicines [3] [4]. Patients have been shown to have poor knowledge and misconceptions about generic medicines [5]. Many studies have reported patients to have negative views about generics as they believe generics to be less effective, of lower quality and unsuitable for treatment of major illnesses, as compared to their branded equivalents [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients have been shown to have poor knowledge and misconceptions about generic medicines [5]. Many studies have reported patients to have negative views about generics as they believe generics to be less effective, of lower quality and unsuitable for treatment of major illnesses, as compared to their branded equivalents [5]- [7]. It is worth noting that some patients might ask the prescriber for a particular drug by name which is usually brand and expensive drug either because of previous experience with the medicine or due to the impact of promotional activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many recipients had received generic tacrolimus after the expiration of the tacrolimus patent. Generic drugs offer significant cost savings for liver transplant programs and recipients; however, there has been considerable concern among transplant hepatologists and patients about the equivalence of the generic and brandname forms [3,6] . Given the lack of adverse events reported and the associated cost savings, conversion from brand-name to generic tacrolimus has been encouraged in organ transplantation [4] .…”
Section: Introductionmentioning
confidence: 99%